2006
DOI: 10.1144/gsl.sp.2006.260.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy, correlations and palaeogeography of Palaeozoic terranes of Bulgaria and NW Turkey: a review of recent data

Abstract: Within the Alpine tectonic units SE of the European Variscan Orogenic Belt in Bulgaria and NW Turkey several crustal blocks are identified. Although their contact relations with surrounding units are obscured by Alpine events, the differences in the succession of events, stratigraphy, sedimentology and palaeobiogeographical distribution within them

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 32 publications
1
39
0
1
Order By: Relevance
“…2: Gözdað, Dolayoba, Istinye and Kartal formations). The macrofaunal and microfaunal data of this period indicate that the palaeogeographic position of the Ýstanbul Terrane remained unchanged compared to the Central European Variscan basins (Haas 1968, Kalvoda et al 2003, Dojen et al 2004, Yanev et al 2006. From Late Devonian onwards, a rapid subsidence and deposition of slope-type sediments (Fig.…”
Section: Geological Setting Of Cebeciköy Limestonementioning
confidence: 87%
See 1 more Smart Citation
“…2: Gözdað, Dolayoba, Istinye and Kartal formations). The macrofaunal and microfaunal data of this period indicate that the palaeogeographic position of the Ýstanbul Terrane remained unchanged compared to the Central European Variscan basins (Haas 1968, Kalvoda et al 2003, Dojen et al 2004, Yanev et al 2006. From Late Devonian onwards, a rapid subsidence and deposition of slope-type sediments (Fig.…”
Section: Geological Setting Of Cebeciköy Limestonementioning
confidence: 87%
“…In western and central Europe, the rock units of this belt and their stratigraphic features have been studied in detail. Towards eastern Europe, the Variscan Belt can be followed in the Balkan (Yanev 1993(Yanev , 1997(Yanev , 2000, NW Anatolian (Göncüoðlu et al 1997(Göncüoðlu et al , 2006 and Caucasian (Yanev & Adamia 2010) terranes (Fig. 1).…”
mentioning
confidence: 99%
“…Görür et al 1997) or Peri-Gondwanan (e.g. Göncüoglu 2001) origin as discussed in detail by Yanev et al (2006). Some indicators such as the type and age of the Neoproterozoic basement of the Istanbul-Zonguldak Terrane (Okay et al 2006), affinity of the Ordovician trilobites with Central Europe, rather than with Baltica (Dean et al 1997;Dean et al 2000) support a Peri-Gondwanan origin.…”
Section: Discussionmentioning
confidence: 98%
“…The thickness of Devonian part is approximately 100 m. Brachiopods (Appendix) in this part of this unit suggest an Early Devonian age . From the lower parts graptolites, conodonts and nautolids of Silurian age are reported (Yanev et al 2006). Recently Boncheva et al (2009) confirmed an age span of Silurian-Early Devonian on the basis of graptolites from the lower part, of acritarchs from the middle part and of the conodonts from the upper part.…”
Section: Litho-and Biostratigraphy Of the Devonian In The çAmdag-zongmentioning
confidence: 93%
See 1 more Smart Citation